Origami Media for Teaching Islamic Cultural History: An Experimental Study in 9th Grade MTs Ma'arif Balong - Umami, Halida; Fajar, Muhammad Dwi; Syarifah, S (Universitas Muhammadiyah Surakarta, 2025)
Islamic Cultural History (SKI) is a subject taught in Madrasahs to help students recognize, understand, and appreciate the values and legacy of Islamic civilization. However, in grade 9 at MTs Ma'arif Balong, student learning outcomes remain below expectations, with an average score of 65, which does not meet the Minimum Mastery Criteria (KKM) of 72. This study aims to examine the effectiveness of origami-based learning media in improving students' learning outcomes in SKI. A quantitative approach with a quasi-experimental design was employed, involving 54 students selected through cluster sampling. Data were collected through written tests and documentation, then analyzed using mean score comparison and the Mann-Whitney test with SPSS software. The results show a significant difference between the experimental and control groups. The experimental group, which used origami as a learning aid, achieved a mean rank of 85.18, while the control group achieved 59.62. The statistical analysis produced a significance value of 0.000 < 0.050, indicating a positive effect of the origami media. These findings suggest that incorporating origami into classroom instruction enhances student engagement, comprehension, and overall academic performance in SKI. The study recommends that teachers develop skills in designing creative instructional media, including origami, and that Madrasahs provide adequate learning materials and a supportive environment. Furthermore, future research is encouraged to investigate the long-term impact of origami-based learning on students' knowledge retention and motivation.